2020
DOI: 10.1155/2020/9510717
|View full text |Cite
|
Sign up to set email alerts
|

Gastritis Stages in Monozygotic and Dizygotic Dyspeptic Twins

Abstract: Background. The progression of Helicobacter pylori-associated gastritis towards atrophic gastritis is modulated by host-related and environmental factors. Studies that explore the possible involvement of host-related versus environmental factors in the development of gastritis phenotype induced by H. pylori are highly needed. Aims. Our study was aimed at investigating the phenotype of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…A recent twin study on peptic ulcer disease focused on the human gut microbiome composition has shown that aging and household-sharing may be the main determinants of gut microbial similarity and drift in both monozygotic and dizygotic twins [43]; however, there was a prominent decline in bacterial similitude with aging [43]. Another twin study indicated that histological gastric mucosa alterations showed high rates of concordance in both monozygotic and dizygotic twins [44], which suggests the importance of both genetic and environmental contributions in peptic ulcer disease. Likewise, in the present study, different environmental or acquired influences may have attenuated the chance of concordance of gastric/duodenal ulcers and cholelithiasis/cholangitis in monozygotic twin pairs compared to that in their dizygotic counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…A recent twin study on peptic ulcer disease focused on the human gut microbiome composition has shown that aging and household-sharing may be the main determinants of gut microbial similarity and drift in both monozygotic and dizygotic twins [43]; however, there was a prominent decline in bacterial similitude with aging [43]. Another twin study indicated that histological gastric mucosa alterations showed high rates of concordance in both monozygotic and dizygotic twins [44], which suggests the importance of both genetic and environmental contributions in peptic ulcer disease. Likewise, in the present study, different environmental or acquired influences may have attenuated the chance of concordance of gastric/duodenal ulcers and cholelithiasis/cholangitis in monozygotic twin pairs compared to that in their dizygotic counterparts.…”
Section: Discussionmentioning
confidence: 99%